Os poderes de coerção do juiz na execução de obrigação de pagar - Nacle, Ricardo Amin Abrahão (2018)
Among the relevant innovations brought by Brazil's 2015 Code of Civil Procedure, the power of enforcement granted to judges with regard to executing obligations to pay is noteworthy. This novelty, which part of the doctrine already understood as applicable even before the repealed code was in force, defines with the powers and duties of the judge to determine atypical measures of enforcement for granting judicial relief to a pecuniary performance. However, the lack of definition of the concept with which the Code worked by giving the technique of atypicality to judges undoubtedly generates a series of questions and fears about possible judicial authoritarianism and violations of the dignity of the debtor. This study will focus on demonstrating that the procedural technique of enforcement acts is fully possible in the obligations to pay and in tune with the fundamental duty to effective judicial protection for the creditor, including by imposing restrictions on the rights of the debtor. It will also demonstrate the unavoidable necessity of the magistrate, when using such procedural techniques, to always do so in accordance with the criteria exhorted by the principle of proportionality